2010
DOI: 10.1111/j.1365-2362.2010.02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on circulating chemerin levels

Abstract: We hypothesize that weight-loss induced reduction in circulating chemerin might in conjunction with other factors be associated with diminished recruitment of macrophages in adipose tissue and reduction of subclinical inflammation, which again could partly explain beneficial long-term effects of weight reduction in obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 12 publications
11
51
2
Order By: Relevance
“…Circulating chemerin levels are known to be associated with obesity in humans (11,15,26,27,28,29). In this study, hepatic chemerin mRNA expression was found to be significantly associated with BMI (R 2 Z0.296; PZ0.039), waist circumference (R 2 Z0.397; PZ0.005), and body fat percentage (R 2 Z0.378; PZ0.008).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Circulating chemerin levels are known to be associated with obesity in humans (11,15,26,27,28,29). In this study, hepatic chemerin mRNA expression was found to be significantly associated with BMI (R 2 Z0.296; PZ0.039), waist circumference (R 2 Z0.397; PZ0.005), and body fat percentage (R 2 Z0.378; PZ0.008).…”
Section: Resultsmentioning
confidence: 52%
“…Several human studies have investigated the association between chemerin levels in the serum and different metabolic disorders (24): obese subjects (BMI O30 kg/m 2 ) have higher plasma chemerin levels than normal-weight subjects (BMI !25 kg/m 2 ) (11,27), and pronounced weight loss after gastric bypass surgery has been reported to decrease serum chemerin levels (15,28,29). An association of circulating chemerin levels with the markers of NAFLD has also been highlighted, but the results have been inconsistent in terms of some of the investigated histological features (28,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the serum chemerin levels were significantly decreased in the male patients with T2DM. The reason for the discrepancy in the relationship between serum chemerin levels and T2DM is unknown; however, studies including the current investigation, have consistently reported that the serum chemerin levels are positively correlated with BMI [12,[16][17][18][19], suggesting that the amount of adipose tissue is a main regulator of the serum chemerin levels.…”
Section: Resultsmentioning
confidence: 58%
“…In particular, serum chemerin levels are closely associated with body mass index (BMI) [12,[16][17][18][19]. Indeed, serum chemerin levels significantly decreased after bariatric surgery according to BMI reduction [18,20].…”
Section: Preparation Of Anti-chemerin Monoclonal Antibodymentioning
confidence: 99%
“…Compared with lean animals, chemerin gene expression is elevated in the adipose tissue of obese animals, and expression levels are markedly elevated during the differentiation of 3T3-L1 cells into mature adipocytes (Bozaoglu et al, 2007). Moreover, chemerin has been suggested to play a role in mediating the long-term beneficial effects of bariatric surgery (Ress et al, 2010). Because chemerin seems to play several roles in both inflammation and metabolism, it has been proposed as a link between chronic inflammation, obesity, and obesity-related comorbidities Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%